Socio-Agricultural Bridging Park: A Conceptual Urban Project in Suburban Area - Uddin, Muhammad Salaha; Ahmed, Kabir (Journal of Bangladesh Institute of Planners, 2012)
Suburban development in large urban region of Europe, North America and Asia continues to erode forest and farm, disrupt hydrological patterns, and weaken the overall ecological integrity of the region. Fragmented landscapes and equally fragmented communities isolate citizens from nature as well as from one another. Alternative design approaches and models for creating sustainable communities are urgently required to address these problems. This paper presents one such conceptual ecological project model, named Socio-Agricultural Bridging Park (SABP) using criteria developed from a wide range of exemplary sustainable community approaches employed over the world. The basic of this project concept is to ascertain a high level of sustainability and to improve a community’s sense of the civic and sense of place. As a part of the study, a suburban area of the city of Milan was selected. In this paper, a local problem of a Suburban area Municipality (Municipality of Settimo Milanese) is addressed and the concept of SABP is approached to solve the problem of fragmented suburban area. The project concept is also linked with the global event world expo-2015 as Milan will host the event. Journal of Bangladesh Institute of Planners, Vol. 5, Dec 2012, pp. 129-138